PENERAPAN KEYAKINAN KELAS DALAM MEMBENTUK PERILAKU SOPAN SANTUN SISWA SDN 15 KUALA MANDOR B - Puteri, Monika (Jurnal Pendidikan Edukasi Kusuma Bangsa, 2025)
Politeness is one of the key elements in shaping students’ noble character and strong personal values. The inculcation of polite behavior from an early age is crucial as it serves as the foundation for building healthy social relationships, both within the school environment and in the broader community. However, based on the findings of the researcher, there has been a noticeable decline in polite behavior among students. This decline is influenced by various factors, one of which is the excessive and uncontrolled use of social media. As a result, some students imitate negative behaviors they observe online, such as speaking rudely, showing disrespect toward elders, and demonstrating a lack of concern for their surroundings. This study aims to reestablish polite behavior in students through the implementation of class agreements at SD Negeri 15 Kuala Mandor B. Class agreements refer to mutual commitments established between teachers and students, developed based on students’ input and jointly agreed upon as rules to be applied consistently throughout the learning process. This research employs a qualitative approach with a case study method. Data collection techniques include interviews, observations, and documentation. Observations were conducted four times during September 2024 to monitor changes in student behavior. The findings reveal that the implementation of class agreements positively influences the improvement of students' polite behavior, both in verbal communication and in their daily attitudes within the school setting. Furthermore, students have begun to demonstrate mutual respect toward one another and show greater respect for their teachers in every learning activity.